Physico-chemical changes in cantaloupe variety glamour during storage - Zainal Abidin, Munira; Shamsudin, Rosnah; Othman, Zaulia; Abdul Rahman, Russly (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
Cantaloupe cultivated in Malaysia appears as the biggest potential in fresh-cut produce industry and offer higher profit returns. From this opportunity, several changes on physico-chemical properties of untreated fresh-cut cantaloupe(variety Glamour) cubes, harvested at ¾ maturity stage, dipped in deionized water for 1 min at 2° C were observed. Changes of total soluble solid (TSS), pH, total acidity (TA), freezing point, and moisture content were determined during 19 days storage at 2° C and 86-87% relative humidity (RH) air. The pH increased from 6.29 to 6.46 and the freezing point varied between -0.98°C and -0.81°C as moisture content increased from 90.89% to 92.38% d.b. The total acidity and TSS decreased with increase in storage time from 0.11% to 0.09% and 9.07 to 8.60 respectively. The results had implication with significant differences (P < 0.1) for the untreated fresh-cut cantaloupe during storage period.